Dynamic factor Value-at-Risk for large heteroskedastic portfolios - Aramonte, Sirio; Giudice Rodriguez, Marius del; Wu, Jason (Journal of Banking & Finance, 2013)
We propose a methodology that can efficiently measure the Value-at-Risk (VaR) of large portfolios with time-varying volatility and correlations by bringing together the established historical simulation framework and recent contributions to the dynamic factor models literature. We find that the proposed methodology performs well relative to widely used VaR methodologies, and is a significant improvement from a computational point of view.